The Research on the Current Logistics Situation and the Dry Port Development of Mongolia - Myagmarsuren, Ochir; Deng, Minrong (Mongolian Journal of International Affairs, 2015)
Nowadays, Mongolia has continually expanded the range of its foreign trade cooperation to include an increasing number of trade partners, which constructed its characteristic mercantile cooperative system, including the two significant neighboring countries, China and Russia, as its strategic partners, the Northeast Asia, as its major imports-exports area, and the increasingly enhanced trade cooperation with the Western countries. Mineral substance is one of the most important exports of Mongolia, which has created considerable foreign exchange receipt. However, as a land-locked country, Mongolia still faces the problems like weak logistics system and backward infrastructure, which impede the further development of the international trade of Mongolia. Building dry ports could shorten the distance between the inland areas and the international markets. Mongolian Journal of International Affairs Vol.19 2014: 56-66